The Role of the Two-Wheel Patrol Unit of the Sabhara Unit in Preventing Motorcycle Theft at Cirebon City Police Department - Wayne, Ronald (Advances in Police Science Research Journal, 2024)
The focus of this thesis is on the role of the two-wheeled patrol unit in the Cirebon City Police Department. The focus of the study taken is considered important because the number of thefts that have occurred in the Cirebon City jurisdiction in the last 3 years has continued to increase. The problems raised in this thesis are: (1) What is the description of criminal acts of theft that occurred at the Cirebon City Police Station?; (2) what role does the 2-wheeled Patorli Sabhara Unit play in preventing criminal acts of theft that occur at the Cirebon City Police Station?; (3) Factors influencing the role of the Sabahara 2-wheeled patrol unit to prevent motor vehicle theft in Cirebon City? In this research, a qualitative approach using the field research method was used. The theories and concepts used are role theory, routine activity theory, management theory, and patrol concept. Techniques for analyzing a thesis use data reduction, data presentation, and drawing conclusions. In the research results found in the field, namely: (1) a description of criminal acts of theft that occurred at the Cirebon City Police Station in general and specifically, namely as an initial analysis in determining targets and roles effectively and efficiently for the 2-wheeled patrol unit sabhara unit. (2) analyzed the role of the sabhara unit in implementing 2-wheeled unit patrols and in the results of the analysis there were still many deficiencies found internally and externally, namely human resources, infrastructure, and also in terms of organization, especially in the 2-wheeled patrol unit of the Cirebon City Police’s sabhara unit. (3) factors that influence the 2-wheeled patrol activities of the Sabhara unit, where the members of the Sabhara unit patrol have not yet taken part in the patrol department and there is a lack of renewal of personnel along with the routes and routes used. (4) in providing the role of 2-wheeled patrol, this sabhara unit requires skills, attitude and knowledge for each member to play a preventive role in carrying out their duties to reduce the number of criminal acts of theft so that in carrying out their duties they can meet the demands of the community. As well as from leadership elements with early detection and also policies that meet the needs of 2-wheeled sabhara patrol units. Based on the research results, the author proposes a suggestion to form a more directed 2-wheeled patrol unit by overcoming the lack of human resources and infrastructure in the Cirebon City Police Station as well as better and more directed organization by the police leadership.